Pyrolysis of waste tyre: article - Mohd Rafee, Nur Atiqah; Alias, Rusmi (2019)
Millions of tyre were produced each and every year and end up as waste tyres because of developing population and fast industrialization. One of the method to convert waste tyre into a valuable product is pyrolysis. The aim of this study is to characterize the liquid product produced by pyrolysis of waste tyre and their characteristics under process parameter such as temperature. In this study, a series of tests were carried out at a various process temperature from 300°C to 500°C. The degaradation of the waste tyre used was identified by TGA analysis and the liquid oil produced were analysed through FTIR and GC-MS analyzer. The oil yield was found to decrease with increasing final pyrolysis temperature and the yield of the gas increased. The highest oil yield was found at 400°C which is 58.3wt.%. The pyrolysis of used tyre at atmospheric pressure commences at about 340°C and completes at around a temperature of 460°C. The influence of temperature showed an increase in the aromatic content of the oil with increasing temperature. However, the aliphatic content decreased. As the temperature was increased from 300°C to 500°C, it was observed that the amount of aliphatic fraction in the oil decreased from 7.8wt.% to 5.4wt.%. In the meantime, the amount of aromatic compounds increased from 37.4wt.% to 51.2wt.%. The main aromatic compounds were limonene, xylene, styrene, toluene, trimethylbenzene, ethylbenzene and benzene.